Cl–···H–N Interaction Assisted Addition of Sulfonamides to Enol Ethers: Synthesis of 2-Deoxy and 2,6-Dideoxy Sulfonamido Glycosides - Mukherji, Ananya; Kancharla, Pavan K. (Synlett, 2022)
The strained/frustrated electrostatic interactions between the ion pair of TTBPy+X– increases the reactivity in both the ions, resulting in the activation of a third molecule like sulfonamides (aromatic/aliphatic) via hydrogen bonding. This intriguing weak-interactions-based reactivity has been utilized to develop an organocatalytic synthesis of 2-deoxy-sulfonamido-glycosides from glycals. The sulfonamidoglycosylation of glycals using a catalytic amount of 2,4,6-tri-tert-butylpyridinium salts proceeded stereoselectively to provide N-glycosides in good to high yields. This process was demonstrated with l-rhamnal and d-galactal. Besides, IR spectroscopic studies explain that the hindered protonated pyridine cannot behave as a cationic Brønsted acid as is generally perceived.
Keywords: N-glycosylation; catalysis; strained Brønsted pairs; stereoselectivity; 2,4,6-tri-tert-butylpyridine.